Disinfection mechanism of E. coli by CNT-TiO2 composites: Photocatalytic inactivation vs. physical separation. (November 2019) - Shimizu, Yuta; Ateia, Mohamed; Wang, Manna; Awfa, Dion; Yoshimura, Chihiro
Abstract: Magnetic carbon nanotube (MCNT) composites with titanium dioxide (TiO2 ) have an enhanced photocatalytic disinfection efficiency (i.e. higher disinfection rate) and better applicability (i.e. solar light applicability and catalyst separation using its magnetic property) than bare TiO2 and/or MCNT. However, the role and mechanism of MCNT in the disinfection process are still unclear. Therefore, this study aimed at investigating the disinfection mechanism of Escherichia coli using MCNT-TiO2 nanocomposites under various conditions (i.e. the presence and absence of light and reactive oxygen species scavengers, and different MCNT-TiO2 ratio) and photocatalytic disinfection models. The results showed that (i) MCNT and its nanocomposites with TiO2 had much higher disinfection efficiencies than bare TiO2, (ii) the physical bacterial capture was the dominant disinfection mechanism, (iii) the higher disinfection rate was found at an optimum MCNT:TiO2 ratio of 5:1 under the tested experimental conditions, (iv) hydroxyl radical (OH) was the influencing reactive oxygen species on the photocatalytic disinfection using MCNT-TiO2, and (v) good correlation between experimental parameters (i.e. carbon contents, surface area and concentration of MCNT-TiO2 ) and the contribution rate of physical and photocatalysis reactions. The finding from this study and the methods proposed herein are essential for understanding the photocatalytic disinfection processes using TiO2 and its carbonaceous nanocomposites, which can promote the application of photocatalytic disinfection process. Graphical abstract: Image 1 Highlights: CNT and its composites with TiO2 had much higher disinfection efficiencies than bare TiO2 . The physical bacterial capture was the dominant disinfection mechanism. The highest disinfection rate was found at an optimum CNT:TiO2 ratio of 5:1. OH was the influencing reactive oxygen species on the photocatalytic disinfection.